Microscale characterization of damage accumulation in CMCs. Issue 5 (May 2021) - Swaminathan, B.; McCarthy, N.R.; Almansour, A.S.; Sevener, K.; Pollock, T.M.; Kiser, J.D.; Daly, S.
Abstract: The developing roles of damage mechanisms in the failure response of SiC/SiC minicomposites was investigated by the characterization of microscale damage accumulation with respect to microstructure. A multi-modal approach combining spatially resolved acoustic emission (AE) with tensile testing in-SEM (scanning electron microscope) was used to simultaneously examine surface (observed in-SEM) and bulk damage (monitored via AE). Strong agreement was shown between the evolving crack density estimated by AE and in-SEM measurements. The following were observed: (i) in-plane matrix content and distribution impacted crack growth; (ii) spatially-distributed matrix cracks generated varying stress-dependent AE; and (iii) certain individual cracks became more probable failure locations due to unique combinations of damage mechanisms that drove their growth. This approach enabled characterizing potential failure determinants and suggests that early damage behavior is related to certain microstructural features (e.g. surface flaws), while subsequent damage behavior is coupled to interactions of local mechanisms evolving with stress.